Genotypical features of the exterior development of Hereford bull-calves - Kolpakov Vladimir; Ruchay Aleksey; Dzhulamanov Kinispay; Gerasimov Nikolay (E3S Web of Conferences, 2020)
An analysis of previous years shows that there is a gradual increase in the rate of breeding and pedigree work, its intensification, which is caused primarily by the implementation of new methods of biotechnology and population genetics. In this regard, the improvement and development of new criteria for cow evaluation taking into account created highly productive lines, types, and populations are relevant for science and practice. There was carried out scientific and economic research in order to characterize the main indicators of the breeding value of cows that belong to the created hornless Ural-type Hereford breed of domestic breeding. The influence of these indicators on the formation of the productivity of bull-calf progenies fell under the characterization as well. There were formed five groups of full-aged cows (5-8 years) different in productive qualities to determine the influence of the productive value of mother cows on the pedigree and productive qualities of progenies. Cows of all groups were inseminated by the deep-frozen seed of Hereford bull of the “elite-record” class produced by Golub 4168. Five groups of experimental bull-calves were formed by the method of groups-analogs from the resulting progeny. The analysis of weight and linear growth of the progeny bull-calves showed that all the animals normally developed being characterized with the general patterns of ontogenesis. At the same time, bull-calf progenies of cows different in productive value were inherent in some features - the average live weight of bulls of group III was larger than those of its peers from groups I, II, IV, and V by 27.4 kg (6.3 %, P>0.95), 64.1 kg (16.1 %, P>0.999), 28.9 kg (6.6 %, P>0.95), and 47.4 kg (11.4 %, P>0.999), respectively.